2013
DOI: 10.1128/aac.02060-12
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Macrolide-Resistant Mycoplasma pneumoniae in Beijing, China, from 2008 to 2012

Abstract: Macrolide resistance rates of Mycoplasma pneumoniae in the Beijing population were as high as 68.9%, 90.0%, 98.4%, 95.4%, and 97.0% in the years 2008 to 2012, respectively. Common macrolide-resistant mobile genetic elements were not detected with any isolate. These macrolide-resistant isolates came from multiple clones rather than the same clone. No massive aggregation of a particular clone was found in a specific period. Mycoplasma pneumoniae is one of the important pathogens causing human respiratory tract i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
123
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(140 citation statements)
references
References 15 publications
13
123
2
2
Order By: Relevance
“…The strains isolated from these two outbreaks were all macrolide resistant; the results may be associated with that finding, though macrolide-resistant strains are common in Asia (23)(24)(25). The small range of the ages of the infected children represents a further limitation, as the students in the two classes were 7 years old and 9 years old, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…The strains isolated from these two outbreaks were all macrolide resistant; the results may be associated with that finding, though macrolide-resistant strains are common in Asia (23)(24)(25). The small range of the ages of the infected children represents a further limitation, as the students in the two classes were 7 years old and 9 years old, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…Between 2002 and 2008, a progressive increase in macrolide resistance from 5 to 39% among M. pneumoniae isolates was observed in Japan and even reached 87% in a recent year (3,26,27). Several Chinese studies reported a higher proportion of macrolide-resistant M. pneumoniae strains, ranging 63 to 92% (13,(28)(29)(30), obtained between 2003 and 2012 from patients with respiratory tract infections. Although it has been reported that the prevalence of macrolide-resistant M. pneumoniae is relatively lower in Europe and the United States, ranging from 3.6% in Germany (31) to 25.6% in Italy (2), the rate of resistance has also increased in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the widespread use of the drug, increasing numbers of macrolide-resistant M. pneumoniae have been reported in the past decade, especially in Asia, Europe, and the United States (6,(10)(11)(12). In China, the infection rate of macrolide-resistant M. pneumoniae has reached up to 90% (13,14).…”
mentioning
confidence: 99%
“…Since approximately the year 2000, macrolide-resistant (MR) M. pneumoniae has been appearing in Asia, Europe, Canada, and the USA (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The rate of macrolide resistance among M. pneumoniae infections ranges from 3 to 26z in Europe (9,15), from 63 to 97z in China (16)(17)(18)(19), and from 25 to 93z in Japan (20)(21)(22). The total number of febrile days and the number of febrile days during macrolide administration are greater in patients infected with MR M. pneumoniae than in patients infected with macrolide-sensitive (MS) M. pneumoniae (23).…”
Section: Introductionmentioning
confidence: 99%